Real-time monitoring of subcellular H2O2 distribution in Chlamydomonas reinhardtii. Issue 9 (1st July 2021) - Niemeyer, Justus; Scheuring, David; Oestreicher, Julian; Morgan, Bruce; Schroda, Michael
Abstract: Hydrogen peroxide (H2 O2 ) is recognized as an important signaling molecule in plants. We sought to establish a genetically encoded, fluorescent H2 O2 sensor that allows H2 O2 monitoring in all major subcompartments of a Chlamydomonas cell. To this end, we used the Chlamydomonas Modular Cloning toolbox to target the hypersensitive H2 O2 sensor reduction–oxidation sensitive green fluorescent protein2-Tsa2ΔCR to the cytosol, nucleus, mitochondrial matrix, chloroplast stroma, thylakoid lumen, and endoplasmic reticulum (ER). The sensor was functional in all compartments, except for the ER where it was fully oxidized. Employing our novel sensors, we show that H2 O2 produced by photosynthetic linear electron transport (PET) in the stroma leaks into the cytosol but only reaches other subcellular compartments if produced under nonphysiological conditions. Furthermore, in heat-stressed cells, we show that cytosolic H2 O2 levels closely mirror temperature up- and downshifts and are independent from PET. Heat stress led to similar up- and downshifts of H2 O2 levels in the nucleus and, more mildly, in mitochondria but not in the chloroplast. Our results thus suggest the establishment of steep intracellular H2 O2 gradients under normal physiological conditions with limited diffusion into other compartments. We anticipate that these sensors will greatly facilitate future investigations of H2 O2 biology in plant cells. Abstract : The establishment of a hypersensitive H2 O2 sensor in six major compartments of the Chlamydomonas cell reveals steep intracellular H2 O2 gradients under normal physiological conditions with limited diffusion into other compartments.